ANALISIS PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Perkebunan Kelapa Sawit PT. Prima Agro Aceh Lestari Kabupaten Aceh Barat) - Arkadius, Ahmad (Jurnal Bisnis Tani, 2018)
As a source of vegetable oil, palm oil is able to become a poverty alleviation tool, food and energy sources. The development of oil palm plantations requires a lot of labor, oil palm plantations are labor-intensive businesses so that the management of occupational health and safety is very important. The purpose of this study was to determine the effect of occupational safety and health on the performance of employees of PT. Prima Agro Aceh Lestari (PAAL) West Aceh District. The results of study showed that workers' protection, worker health maintenance and workplace safety had a positive effect and had a strong relationship to employee performance. Simultaneously, worker protection, maintenance of workers' health and safety in the workplace relate to employee performance, but partially only worker protection and worker health maintenance that affect employee performance. In addition to the research variables there are still other factors that are also strong in influencing the performance of employees of PT. Prima Agro Aceh Lestari (PAAL).